MUHAMMED ASAD - IZMEĐU RELIGIJE I POLITIKE - Asad, Talal; Karić, Dženita (Novi Muallim, 2022)
Tekst preuzet sa web stranice: http://islaminteractive.info/content/ muhammad-asad-between-religion-and-politics (pristupljeno 23.5.2012) Prijevod s engleskog: Dženita Karić